Pearl Squires on rock's by river in St. Philip's - Squires, Allen; Squires, Pearl (1962)
Photograph of Pearl Squires on rock's by river in St. Philip's. Pearl Squires slide label reads “Me on rocks by river St. Philips NF. Little Derick and friend in distance.”